EFEKTIFITAS PENDIDIKAN POLITIK TENTANG PEMILU 2024 TERHADAP PENYANDANG DISABILITAS DI PANTI SOSIAL BINA LARAS SENTOSA II OLEH KPU JAKARTA TIMUR - Sigalingging, Yusuf Christian (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research focuses on the effectiveness of the East Jakarta KPU's political education on the understanding of people with disabilities regarding the 2024 elections. The aim of this research is to determine the effectiveness of the KPU's political education in East Jakarta and to determine the understanding of political education carried out by the East Jakarta KPU for residents of the Bina Laras Harapan Sentosa social institution II. The research method used is a qualitative approach using an exploratory descriptive type of research. Data collection techniques used interviews and literature study. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The theory used is the theory of program effectiveness and political education. The results of this research indicate that the socialization activities carried out by the East Jakarta KPU at PSBL II were effective if assessed using Campbell J.P.'s theory. which consists of 4 indicators, namely program success, target success, satisfaction with the program and achievement of overall goals